System Usability Sclae Aplikasi Kitabisa Dengan Evaluasi Metode Design Thinking - Dionisius Chandra Irawan; Mochzen Gito Resmi; Uus Muhammad Husni Tamyiz (Institut Pendidikan Indonesia, 2022)
In the rapid development of technology, many people, especially in Indonesia, many things change when technology is increasingly updated and makes users feel comfortable. People use Kitabisa to donate or raise funds for various purposes. Some focus on medical purposes, but actually there are many other categories. SUS testing is efficient and the data produced is reliable. Redesign means updating an item that already exists but is less efficient to use. Design Thinking is the collection of human needs that allow them to be fulfilled technologically and efficiently. The SUS test got a result of 59.6 with the Redesign stage then carried out with the intent and purpose of overcoming the problems that occur at this time. then the Kitabisa application gets an increase in value from the previous 59.6 to 73 then the results of this test have increased so that it can be said to be getting better than before